Patrimônio cultural do Amapá: o caso das louceiras do Maruanum em observância ao princípio da equidade intergeracional - COSTA, Célia Souza da (2014)
The women in the communities of Santa Luzia and the Carmo Maruanum belonging to Maruanum District in the city of Macapa in Amapá practice for centuries the tradition of the craft potter . Based on the pioneering study by researcher Alicia Coirolo in 1989 in the District of Maruanum and published by the Goeldi Museum Bulletin in 1991 that emphasizes the risk of extinction of rear- know-how of the craft of the potters Maruanum the need arose in search as this rear- know-how survived over time after first search. The central objective of this case study was to analyze the craft of the potters Maruanum as cultural heritage material and immaterial considering the principle of intergenerational equity , find out how to create know-how - the potter craft was being practiced in order to describe the changes occurring in the process of doing the dishes and the reasons for the potter tradition is disappearing while . The methodology was hypothetical-deductive approach with qualitative and quantitative data based on apparent from the literature , documentary and field research in the communities of Santa Luzia and the Carmo Maruanum and public agencies related to cultural heritage , with the use of focused interviews structured and unstructured on the perception of rear- know- the tableware and actions to potter tradition in cultural context . The results confirmed the imminent risk of extinction of the rear- know-how of the craft potter in the two communities studied , the negative effect of welfare programs of the federal and state government that encourages disregard for traditional practice , the need for registration and other guardianships possible for the official recognition of the craft of the potters Maruanum as cultural heritage of the state of Amapá and the urgency of the practice of a plan to safeguard that would encourage young people to continue with the tradition of rear- know-how of crockery.